Identification of Core Genes Shared by Endometrial Cancer and Ovarian Cancer Using an Integrated Approach: Core Genes Shared by Endometrial and Ovarian Cancers - Ke, Yumin; Zhuang, Xuanxuan; You, LiuXia (Cellular and Molecular Biology, 2022)
Ovarian cancer (OC) is one of the most commonly diagnosed cancers among women. Moreover, Endometrial cancer (EC) is a usual genital tract cancer in females; however, the hub genes and molecular pathways shared by these two cancers have not been surveyed yet. So, this study aimed to identify the common candidate genes or biomarkers and molecular pathways in OC and EC. Differences in the expressed genes between these two microarray data sets were detected. Pathway enrichment analysis and gene ontology (GO) was also performed and protein-protein interactions (PPI) network analysis was done using Cytoscape and the most important genes were identified by the Cytohubba plugin. We found that 154 common DEGs shared by OC and EC were also detected. 10 hub proteins were identified as follows: CDC20, BUB1, CENPF, KIF11, CCNB2, FOXM1, TTK, TOP2A, DEPDC1, and NCAPG. The most important and significant miRNAs were identified to be hsa-mir-186-5p, hsa-mir-192-5p, hsa-mir-215-5p, and hsa-mir-193b-3p regulated expressions of the DEGs. This investigation demonstrated that these hub genes and their miRNA might be key genes with great effects on OC and EC. However, more studies are needed for a better understanding of the role of these hub genes and their function in these two cancers.